Eremitis pernambucensis (Poaceae, Bambusoideae), a new species of herbaceous bamboo, marks the northernmost distribution of the genus in Brazil - Ferreira, Fabrício Moreira; Welker, Cassiano A. Dorneles; Clark, Lynn G.; Oliveira, Reyjane P. (Phytotaxa, 2024)
Eremitis pernambucensis F.M.Ferreira & R.P.Oliveira (Poaceae, Bambusoideae), a new species of herbaceous bamboo from the state of Pernambuco, Brazil, is described and illustrated, and the characters distinguishing it from E. victoriae F.M.Ferreira & R.P.Oliveira are discussed. The new species described here represents the first record of Eremitis in this Brazilian state and the northernmost distribution of the genus known so far.